2012
DOI: 10.1260/1369-4332.15.4.589
|View full text |Cite
|
Sign up to set email alerts
|

Composite Behaviour of a Hybrid FRP Bridge Girder and Concrete Deck

Abstract: This paper involves experimental investigation onto the composite behaviour of a hybrid FRP bridge girder with an overlying concrete deck. Two types of shear connections were investigated: epoxy resin adhesives alone and epoxy resin combined with steel u-bolts. The results showed that the steel u-bolts combined with epoxy resin provided a more effective connection; hence a full-size specimen was prepared based on this result. Four-point bending test was carried out to determine the behaviour of a full-scale co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 4 publications
(1 reference statement)
1
19
0
Order By: Relevance
“…This process initiates hairline cracks in the concrete that progress into wide cracks, which significantly reduces the ultimate axial capacity and leads to the brittle failure behavior of concrete columns owing to the damage to the lateral reinforcement (Pantelides, et al, 2013). Steel corrosion costs the Australian economy more than $13 billion per year (Cassidy, et al, 2015), while Canada and the US spend from $50 to 100 billion on repairing deteriorated concrete structures (Tannous, 1997;Manalo, et al, 2012). This issue has motivated many researchers around the world to investigate the use of high-strength and non-corroding reinforcement in building new concrete structures.…”
Section: Introductionmentioning
confidence: 99%
“…This process initiates hairline cracks in the concrete that progress into wide cracks, which significantly reduces the ultimate axial capacity and leads to the brittle failure behavior of concrete columns owing to the damage to the lateral reinforcement (Pantelides, et al, 2013). Steel corrosion costs the Australian economy more than $13 billion per year (Cassidy, et al, 2015), while Canada and the US spend from $50 to 100 billion on repairing deteriorated concrete structures (Tannous, 1997;Manalo, et al, 2012). This issue has motivated many researchers around the world to investigate the use of high-strength and non-corroding reinforcement in building new concrete structures.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the load-slip behavior of the shear FRP-concrete hybrid connections is different from that in steel-concrete composite systems [19,25,26], the conventional design method provided in Eurocode 4 [32] was used in bridge design. It was assumed, that the welded bolts transmitted the longitudinal shear force between the concrete and the FRP beam, ignoring the effect of natural bond between the two and neglecting adhesive bond as well.…”
Section: Shear Connection Designmentioning
confidence: 99%
“…In fact, there are several advantages with the FRP-concrete hybrid girders, referring to the increase of flexural stiffness thus reducing deformability and preventing the buckling phenomena of the FRP profiles or shells. Moreover, the "pseudo-ductile" behavior, necessary for bridges and the existence of composite action between the FRP beam and the concrete slab are a serious advantage of these girders [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 To overcome these obstacles, a number of researchers have worked to combine FRP and conventional materials. [6][7][8][9] Hollaway 10 previously reported that FRP materials were most effectively used in combination with concrete or light-weight foam in sandwich or hybrid composite structures.…”
Section: Introductionmentioning
confidence: 99%